Penempatan dan kehidupan komuniti Bajau Laut di Pulau Gusungan, Semporna - Ismail Ali (University of Malaya, 2008)
The purpose of this article is to document a small and unique island inhabited by the Bajaus, known as Gusungan Island in Semporna, Sabah. The islands documentation is based on written notes taken when a field work was done on the several islands in Semporna for eco-tourism. Although this island is the main access to Sipadan, Mabul, Kapalai, Si Amil and Ligitan islands, its existence in Semporna and the Sulu Sea is not noticed by the local public, and often the source of tale by the outsiders, specially tourists, who have no efforts to do research to make this island known to the local populace. Moreover, the disquieting disappearance of Kapalais history from sight should be a lesson to everyone. This article is written with the intention of documenting Gusungan Islands existence and its occupants (the Bajau sea community) and be seen as the pearl in the secluded dessert of the Sulu Sea, that would probably in time, receive the same fate as that of Kapalai Island, lost without leaving its history behind.